Święto Nocy Walpurgi jako fenomen kulturowo-literacki (na podstawie analizy porównawczej tragedii „Faust” J.W. Goethego i powieści „Mistrz i Małgorzata” M. Bułhakow - Anna Chudzińska-Parkosadze (Studia Rossica Posnaniensia)
The article is devoted to the phenomenon of Walpurgis Night in European culture and literature. The author focuses on the contradictions in the notion and images of Walpurgis Night, which emerged as a result of centuries of Catholic education in Europe. As a matter of fact, the feast named after Saint Walpurga is the pagan feast of Beltane, the scared night of love, vigor and awakening new life. Such a concept of the event is reflected in two masterpieces of world literature — Johann Wolfgang von Goethe's tragedy Faust and the novel The Master and Margarita by Mikhail Bulgakov.